2012
DOI: 10.1161/strokeaha.111.646687
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Mobilization Within 24 Hours of Acute Stroke

Abstract: Background and Purpose-Very early mobilization (VEM) is considered to contribute to the beneficial effects of stroke units, but there are uncertainties regarding the optimal time to start mobilization. We hypothesized that VEM within 24 hours after admittance to the hospital would reduce poor outcome 3 months poststroke compared with mobilization between 24 and 48 hours. Methods-We conducted a prospective, randomized, controlled trial with blinded assessment at follow-up. Patients admitted to the stroke unit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 43 publications
5
71
0
18
Order By: Relevance
“…[25][26][27][28] A favourable outcome for the VEM group was also observed in a similar pilot trial in the UK 27 and in an individual-patient meta-analysis of two small EM trials. 28 However, a non-significant increase in unfavourable outcome was reported in a more recent small Norwegian trial 65 comparing VEM (< 24 hours) versus later mobilisation (> 24 hours). It is not yet clear if the results of the current AVERT are simply providing greater precision around these smaller estimates or if there is some qualitative difference in the nature of the intervention.…”
Section: Statistical Trial Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[25][26][27][28] A favourable outcome for the VEM group was also observed in a similar pilot trial in the UK 27 and in an individual-patient meta-analysis of two small EM trials. 28 However, a non-significant increase in unfavourable outcome was reported in a more recent small Norwegian trial 65 comparing VEM (< 24 hours) versus later mobilisation (> 24 hours). It is not yet clear if the results of the current AVERT are simply providing greater precision around these smaller estimates or if there is some qualitative difference in the nature of the intervention.…”
Section: Statistical Trial Resultsmentioning
confidence: 98%
“…Results are presented as the OR (95% CI) of the early versus delayed mobilisation group. 65 Bernhardt 35 AVERT 31 Chippala 60 Chippala 63 Poletto 61 Herisson 62 T his project met its initial objectives of effectively delivering our VEM protocol with a resulting change in practice. 30 We observed earlier, more frequent and higher dose (amount of) out-of-bed mobility in terms of sitting, standing and walking activity.…”
Section: Statistical Trial Resultsmentioning
confidence: 99%
“…6 It has been shown that platelet function 21 and outcome in experimental stroke studies depend on age 22,23 and comorbidities. 24 Nevertheless, and despite consensus statements such as the Stroke Treatment Academic …”
Section: Discussionmentioning
confidence: 99%
“…Sundseth и соавт. [23] провели рандомизиро-ванное исследование, в котором сравнивали эффек-ты мобилизации пациентов в 1-е сутки (27 человек) и на 2-е сутки (29 человек) после инсульта. В группе мобилизации в 1-е сутки после инсульта через 3 мес отмечались худшие исходы (выше летальность и сте-пень инвалидизации), в то же время у пациентов, ко-торые были мобилизированы в течение 2-х суток по-сле инсульта, отмечался меньший неврологический дефицит, однако эти различия не достигли статисти-ческой значимости.…”
unclassified
“…В группе мобилизации в 1-е сутки после инсульта через 3 мес отмечались худшие исходы (выше летальность и сте-пень инвалидизации), в то же время у пациентов, ко-торые были мобилизированы в течение 2-х суток по-сле инсульта, отмечался меньший неврологический дефицит, однако эти различия не достигли статисти-ческой значимости. Авторы подчеркивают, что не-большое число пациентов в исследовании не позво-ляет делать однозначных выводов по полученным результатам [23]. Анализ факторов, которые могли бы объяснить лучшие исходы в когорте пациентов, не выявил какой-либо конкретный фактор [24].…”
unclassified